a)5/12 + 1/4 =
b)23/5 - 11/3 =
c)4/5 + 13 =
d)8/5 : 1/3 =
e)3/7 x 2 =
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bai 2 :
\(\hept{\begin{cases}x+y=7\\x-7=13\end{cases}\Leftrightarrow\hept{\begin{cases}x+y=7\\x=20\end{cases}}}\)
Thay x vào phương trình đầu ta có :
\(20+y=7\Leftrightarrow y=-13\)
Vậy \(\left\{x;y\right\}=\left\{20;-13\right\}\)
Thử \(20-13=7\); \(20-7=13\)( thỏa mãn )
`a)1 4/23 + ( 5/21-4/23)+16/21-1/2`
`=27/23+5/21-4/23+16/21-1/2`
`=(27/23-4/23)+(5/21+16/21)-1/2`
`=23/23+21/21-1/2`
`=1+1-1/2`
`=2-1/2`
`=4/2-1/2`
`=3/2`
___
`b)75%-(5/2+5/3)+(-1/2)^3`
`=3/4-5/2+5/3+(-1/8)`
`=(3/4-5/2-1/8)+5/3`
`=(6/8-20/8-1/8)+5/3`
`=-15/8+5/3`
`=-45/24+40/24`
`=-5/24`
___
`c)-3/4(-55/9).8/11`
`=-3/4.(-40/9)`
`=-10/3`
__
`d)-3/8 . 6/13 + 7/13 . (-3/8) + 1 3/8`
`= -3/8 . (6/13 + 7/13) + 11/8`
`= -3/8 . 13/13 + 11/8`
`= -3/8 .1 + 11/8`
`= -3/8 + 11/8`
`= 8/8`
`=1`
c) Ta có: \(\dfrac{3}{5}+\dfrac{-5}{20}+\dfrac{30}{75}+\dfrac{-7}{4}\)
\(=\dfrac{3}{5}+\dfrac{2}{5}+\dfrac{-1}{4}+\dfrac{-7}{4}\)
\(=1-2=-1\)
Giải:
a)-1/12+4/3=-1/12+16/12=15/12=5/4
b)(-4/14-3/15)-(1/5-20/35-(-1)).7
=-17/35-22/35.7
=-17/35-22/5
=-171/35
c)3/5+-5/20+30/75+-7/4
=3/5+-1/4+2/5+-7/4
=(3/5+2/5)+(-1/4+-7/4)
=1+-2
=-1
d)5/6.-12/14+7/13
=-5/7+7/13
=-16/91
e)2/-9-5/-36-1/4
=-1/12-1/4
=-1/3
f)2/23+-5/12+7/18+21/23+-7/12
=(2/23+21/23)+(-5/12+-7/12)+7/18
=1+-1+7/18
=7/18
a)5/12 + 1/4 = \(\dfrac{5}{12}+\dfrac{3}{12}=\dfrac{8}{12}=\dfrac{2}{3}\)
b)23/5 - 11/3 = \(\dfrac{69}{15}-\dfrac{55}{15}=\dfrac{14}{15}\)
c)4/5 + 13 = \(\dfrac{4}{5}+\dfrac{65}{5}=\dfrac{69}{5}\)
d)8/5 : 1/3 = \(\dfrac{8}{5}x3=\dfrac{24}{5}\)
e)3/7 x 2 =\(\dfrac{6}{7}\)
\(a,\) \(\dfrac{5}{12}+\dfrac{1}{4}=\dfrac{5}{12}+\dfrac{3}{12}=\dfrac{8}{12}=\dfrac{2}{3}\)
\(b,\) \(\dfrac{23}{5}-\dfrac{11}{3}=\dfrac{69}{15}-\dfrac{55}{15}=\dfrac{14}{15}\)
\(c,\) \(\dfrac{4}{5}+\dfrac{1}{3}=\dfrac{12}{15}+\dfrac{5}{15}=\dfrac{17}{15}\)
\(d,\) \(\dfrac{8}{5}:\dfrac{1}{3}=\dfrac{8}{5}\times\dfrac{3}{1}=\dfrac{24}{5}\)
\(e,\) \(\dfrac{3}{7}\times2=\dfrac{3\times2}{7}=\dfrac{6}{7}\)